Ratification of International Configuration of Labour Organization to Law Number 18 Years 2017 - Uzlifatus Dea Arianty*; Elverda Nadifa Rosyadi; Farizza Taralita Arrachma Fachrezzi; Azizah Kaltsum Mabrukah; Era Titis Cahya Rani (Riwayat: Educational Journal of History and Humanities, 2023)
International Conventions which are attended by various countries aim to establish relations, and create world peace, and can be a source of international law. The ILO Convention is one of the Conventions which is the reason why several Conventions have been ratified into Legislation. One of the products of ratification issued by the Government of Indonesia is Law Number 18 of 2017. This law contains the rights of workers or laborers, so it is hoped that the ratification will create gaps and guarantee security, as well as comfort for workers who are in the area. Indonesian country. The obligations of the state, the implications for the state and its citizens, the form and process of ratification are also important aspects in carrying out and ratifying the ratification. The explanation regarding this matter will certainly expand and widen in relation to the provisions that have been stipulated in Indonesian positive law and involve several parties to assist in the adjustment process and existing provisions on the basis of the state.